Pengaruh Perubahan Sosial Terhadap Peran Gender dalam Masyarakat di Kecamatan Manggala Kota Makassar Perspektif Hukum Islam - Salsabila, Shabrina Syifa; Kadafi, Muh.; Maloko, M. Thahir (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Culture and religion have an important role in shaping values, norms and views regarding gender roles and status in society. Viewed from a contemporary perspective, the influence of culture and religion on gender justice Perspektif Kontemporer is very complex and varied. Culture can influence gender equality by reinforcing unequal gender views and judgments between men and women. Religion also plays an important role in gender justice in a contemporary perspective. Certain religious interpretations and practices can reinforce unequal gender norms and roles. There are several religions that have rules and traditions that give men higher power than women in social and religious structures. The aim of the research is to understand how culture and religion influence gender justice from a contemporary perspective. The method used in this research is an exploratory oriented qualitative research method which attempts to analyze research problems from reading sources by applying content analysis. Researchers use qualitative research to examine the results of previous research and to interpret a phenomenon scientifically. Data collection techniques were carried out through documentation techniques from various journals, proceedings, online news and relevant books. The results of this research show that there is a better understanding of the influence of culture and religion on gender justice from a contemporary perspective. The conclusion of this research is to show that a better understanding of the influence of culture and religion will be able to build a society that is more inclusive and equal between all individuals, regardless of gender.